Processing of Polymer Nanocomposites - Kenig, Samuel, ditor 648744; ScienceDirect (Online service) 7722 (Cincinnati : Munich Hanser Publications, 2019)
This book covers the fundamental unit operations involved in processing of thermoplastic and thermoset nanocomposites. The processing methods include extrusion, injection molding, blow molding, and thermoforming. Also covered are nanoparticle dispersion, distribution, and compatibilization, and applications of polymer nanocomposites.